The effect of etomidate or propofol on brainstem function during anesthesia induction: a bispectral index-guided study - Zheng H; Zhu Y; Chen K; Shen X (Dove Medical Press, 2019)
Huibao Zheng,* Yuexin Zhu,* Kaizheng Chen, Xia ShenDepartment of Anesthesiology, The Eye, Ear, Nose and Throat Hospital of Fudan University, Shanghai Medical College of Fudan University, Shanghai, People’s Republic of China*These authors contributed equally to this work Purpose: To compare the effect of etomidate versus propofol infusion on hemodynamic profiles, spontaneous breathing, and corneal reflex during the induction of anesthesia.Methods: Adult patients (n=80) were randomized to receive etomidate (Group E, n=40) or propofol (Group P, n=40) infusion during anesthesia induction. Throughout induction, mean blood pressure and heart rate were monitored. Time to loss of consciousness (LOC), bispectral index (BIS), existence of spontaneous breathing, and corneal reflex at LOC were recorded.Results: Fewer changes in hemodynamic profile occurred in Group E compared with Group P during induction of anesthesia. The mean time to LOC was shorter with etomidate than propofol (129.5 s vs 189.5 s, P<0.0001). BIS was lower in Group E compared with Group P at LOC (46.3 vs 52.9, P=0.0141). More patients exhibited spontaneous breathing in Group E compared with Group P at LOC (80% vs 17.5%, P<0.0001). Similarly, more patients maintained corneal reflex in Group E compared with Group P (34 patients vs 4 patients, P<0.0001). The incidence of etomidate-induced myoclonus was 17.5%.Conclusion: Compared with propofol infusion, etomidate infusion during anesthesia induction had fewer effects on the hemodynamic profile of patients. Among patients who received etomidate, the BIS value was lower at LOC, and more patients displayed spontaneous breathing and corneal reflex.Trial Registry Number: China Clinical Research Information Service, ChiCTR-IOR-17011050Keywords: anesthesia, etomidate, propofol, consciousness monitors, bispectral index